Impact of Medicare Part D on Racial and Ethnic Minorities - Jamison, JoEllen Jarrett (Divers Equal Health Care, 2016)
OBJECTIVES: Prior to the implementation of Medicare Part D in the United States, inequalities were found to exist in the use of medications between minority and white beneficiaries. Despite improvements in medication affordability after Medicare Part D implementation, it is still not clear whether the characteristics of the program have improved drug utilization patterns among minorities to the same degree as whites. This review aims to determine whether there were barriers for Medicare Part D to realize its potential to improve prescription drug utilization patterns among minorities. METHODS: Google Scholar, PubMed, Sciencedirect and Scopus were used to conduct a comprehensive search of the literature published since 2003 when the Medicare Prescription Drug, Improvement, and Modernization Act (MMA) was passed, which authorized the establishment of the Part D program. All studies and documents related to the effects of Medicare Part D on minorities were included to present a relatively comprehensive review on the topic. RESULTS: Evidence indicated that minorities are not equally benefiting from Medicare Part D prescription drug coverage compared to whites. Examples of characteristics of Medicare Part D that caused significant racial differences in drug utilization include the donut hole, the complexity and number of drug plans, and drug utilization management strategies. CONCLUSION: Medicare Part D has increased access to prescription medications for the elderly. However, continued analysis and research of drug utilization patterns among minorities should be conducted to ensure that all enrollees regardless of race are benefiting equally from Medicare Part D. Identification of these barriers can provide insights on how to improve the program to allow minorities to benefit equally from the Medicare Part D program and remove health inequalities.